THE PERSONALITY OF THE MAIN CHARACTER AS REFLECTED IN PAULO COELHO’S THE DEVIL AND MISS PRYM: A PSYCHOLOGICAL STUDY - Fitri Palupi Kusumawati (Premise: Journal of English Education and Applied Linguistics, 2013)
This research entitled “The Personality of the Main Character as Reflected in Paulo Coelho’s The Devil and Miss Prym” is intended to find out the personality of the main character and factors that influence the personality of the main character. This research uses descriptive qualitative method since the researcher does not apply any quantitative analysis or statistical procedures. The researcher uses the novel entitled The Devil and Miss Prym as the data source of the research. The methods used in collecting the data are observation and documentation. In observation method, the researcher reads the chosen object critically, and then identifies the psychological conflicts. After reading and identifying, the researcher collects and writes all data supporting the research. While in the documentation method, the researcher uses some related books and other documents collected from internet to support this research. In analyzing the data, the researcher applies descriptive qualitative method. He uses the descriptive qualitative method to collect the data and analyzes it by using Sigmund Freud’s personality theory. The result shows that the personality of the main character is influenced by internal and external factors. The internal factor consists of heredity features relating to physic, psychological features relating to physical state, and the heredity features of the character. The external factor consists of some part of life like family, environment, and job.